TRPA1 Channels Modify TRPV1-Mediated Current Responses in Dorsal Root Ganglion Neurons - Masuoka, Takayoshi; Kudo, Makiko; Yamashita, Yuka; Yoshida, Junko; Imaizumi, Noriko; Muramatsu, Ikunobu; Nishio, Matomo; Ishibashi, Takaharu (Frontiers in Physiology, 2017)
The transient receptor potential vanilloid 1 (TRPV1) channel is highly expressed in a subset of sensory neurons responsible for nociception in the dorsal root ganglia (DRG) and trigeminal ganglia of experimental animals. Some TRPV1-positive neurons were reported to coexpress the transient receptor potential ankyrin 1 (TRPA1) channel whose activities are closely modulated by TRPV1 channel. However, whether TRPV1 channel activities are modulated by TRPA1 channels in primary sensory neurons remains to be clarified. This study demonstrates the difference in electrophysiological responses induced by TRPV1 channel activation between TRPA1-positive and TRPA1-negative DRG. TRPV1 and TRPA1 channel activations were evoked by capsaicin (1 μM), a TRPV1 agonist, and allyl isothiocyanate (AITC; 500 μM), a TRPA1 agonist, respectively. Capsaicin perfusion for 15 s caused a large inward current without a desensitization phase at a membrane potential of −70 mV in AITC-insensitive DRG (current density; 29.6 ± 5.6 pA/pF, time constant of decay; 12.8 ± 1.8 s). The capsaicin-induced currents in AITC-sensitive DRG had a small current density (12.7 ± 2.9 pA/pF) with a large time constant of decay (24.3 ± 5.4 s). In calcium imaging with Fura-2, the peak response by capsaicin was small and reaching the peak response took a long time in AITC-sensitive neurons. These electrophysiological differences were completely eliminated by HC-030031, a TRPA1 antagonist, in an extracellular solution or 10 mM EGTA, a Ca2+ chelator, in an internal solution. Capsaicin perfusion for 120 s desensitized the inward currents after a transient peak. The decay during capsaicin perfusion was notably slow in AITC-sensitive DRG; the ratio of the capsaicin-induced current 60 s after treatment per the peak current in AITC-sensitive neurons (78 ± 9%) was larger than that in AITC-insensitive neurons (48 ± 5%). The capsaicin-induced current in the desensitization phase was attenuated by HC-030031 in AITC-insensitive DRG. These results indicate that in TRPA1-positive neurons, (1) the TRPV1-mediated currents are of small densities with slow decay, and are caused by TRPA1 channel activities and intracellular Ca2+ mobilization and (2) desensitization of TRPV1-mediated current is apparently slow, due to appending TRPA1-mediated current.